Genetic parameters of lifetime traits in Hariana cattle - S. Singh; Z.S. Rana; S.S Dhaka; B.L. Pander (Journal of Livestock Biodiversity, 2025)
The data pertaining to lifetime traits of 762 Hariana cows born to 23 sires and spread over a period of 35 years (1966 to 2000) maintained at Government Livestock Farm, Hisar were considered for the estimation of genetic parameters. The least square means for number of lactations completed (NLC), herd life (HL), lifetime milk yield (LTMY), productive life (PL), milk yield per day of productive life (MYPDPL) and milk yield per day of herd life (MYPDHL) were obtained as 5.15±0.43, 2260.14±152.24 days, 6420.29+524.21 kg, 1284.54+94.42 days, 4.49+0.17 kg/day and 2.58+0.13 kg/day, respectively. The effects of period and season of calving and age at first calving were statistically non-significant on all the lifetime traits under study. However, autumn season calvers excelled in performance while the least square means for NLC, PL and MYPDHL were the lowest for the rainy season calvers and for the rest of lifetime traits; it was the lowest for summer calvers. All the lifetime traits had low estimates of heritabilities, ranging from 0.070 to 0.192, except the heritability estimates for MYPDPL, which was moderate. All the lifetime traits had high, positive genetic and phenotypic correlations among themselves, which ranged from 0.906 to 0.990 and 0.373 to 0.938, respectively. It may be inferred that the selection on the basis of MYPDPL will help in the improvement of other traits through correlated response.